1984
DOI: 10.1159/000242071
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cysteine Dioxygenase and Cysteinesulfinate Decarboxylase Activities and Taurine Levels in Tissues of Pregnant or Lactating Rat Dams and Their Fetuses or Pups

Abstract: The level of taurine and the activities of the two enzymes involved in its synthesis, cysteine dioxygenase and cysteinesulfinate decarboxylase, were measured in tissues of rat dams during pregnancy and lactation and in their fetuses or pups. The most marked changes observed in the dams included an increased hepatic taurine concentration in late pregnancy (20 days), a decreased plasma taurine concentration during late pregnancy and throughout lactation, and a decrease in tissue cysteine dioxygenase activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…It has been demonstrated that the liver is the main organ of taurine synthesis [16] and that the milk taurine level is positively correlated with hepatic taurine concentration during the lactational period [26]. The hepatic taurine may serve as a source of taurine for secretion into the milk.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the liver is the main organ of taurine synthesis [16] and that the milk taurine level is positively correlated with hepatic taurine concentration during the lactational period [26]. The hepatic taurine may serve as a source of taurine for secretion into the milk.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is an endogenous partial agonist of the GABA A R and induces chloride currents in neurons (Linne et al, 1996; Ye et al, 1997). Although the capacity to synthesize taurine is low during fetal life (Hayes and Sturman, 1981; Kuo and Stipanuk, 1984; Ghisolfi, 1987), taurine levels are higher in the immature brain than in the adult brain (Kaczmarek, 1976; Benitez-Diaz et al, 2003). In mammals, sufficient taurine for embryonic development is received from the mother via the placenta, while neonates obtain taurine from their mothers’ milk (Sturman et al, 1977; Sturman, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis of taurine is decreased in most developing mammals due to reduced activity of the rate-limiting enzyme, cysteine sulfinic acid decarboxylase (5,16). Although measurement of in vitro enzyme activity may not accurately reflect in vivo biosynthetic rates, the decreased CSAD activity observed during development implies that exogenous sources of taurine play an important role in maintenance of tissue stores (6).…”
Section: Resultsmentioning
confidence: 99%
“…During development, maintenance of intrahepatic taurine stores could be of particular importance inasmuch as bile flow is already diminished and exposure to oxidant stress is increased (1 1, 2 1, 22). In addition, taurine biosynthesis and the capacity of the kidney to retain taurine are decreased in the immature animal (5,16,23). Under these conditions, an efficient transport system for taurine uptake from portal blood might prevent intracellular depletion of this p-amino acid.…”
Section: Resultsmentioning
confidence: 99%